The Increase of Self Personal Hygiene Patient with Hallusination by Nursing Methods of Partisipatif and Rewards Approach - Sirajudin Noor; Heny Desyi Rubiyana; Adijani al-Alabij (Universitas Airlangga, 2012)
Introduction: The number of mental disorder has been increased dramatically and it is predicted that one out of four citizen suffered with mental disorder. The commonest problem for the patient schizophrenia with hallusination is unfullﬁll of basic needs. The objective of the study was to analyse the effect of partisipatif and reward approach on the need of basic human in term of feeding, toileting, dressing, bathing, and moving patient with halusination Sambang Lihum hospital in Banjarmasin.Methods: Design of the study was pra-experimental, static-group comparison design. Fifty ﬁve (55) sampel was recruited by purposive sampling for patient schizophrenia with halusination stabil condition and calm.The sample were divided into two goups contol and intervention group. Data were collected by check list and observation of the status of self personal care. Data were analysed by wilcoxon and Mannwhitney with signiﬁcancy level α < 0.05.Result: Result showed that methods of partisipatif and rewards effect on the self personal hygiene for the patient with hallusination, with p = 0.001.Conclusion: Partisipatif and reward methods was effective on the increase of self personal hygienne for the patient with hallusination.